2013
DOI: 10.1002/bmc.2862
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–tandem mass spectrometric assay for the determination of tetrabenazine and its active metabolites in human plasma: a pharmacokinetic study

Abstract: A simple, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method has been developed and fully validated for the simultaneous quantification of tetrabenazine and its active metabolites α-dihydrotetrabenazine and β-dihydrotetrabenazine in human plasma. Tetrabenazine d7 was used as internal standard (IS). The analytes were extracted from 200 μL aliquots of human plasma via solid-phase extraction using C18 solid-phase extraction cartridges. The reconstituted samples were chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was required that greater than two‐thirds of reanalyzed samples had a relative difference in concentration of within 20% of the original assay (Derangula et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…It was required that greater than two‐thirds of reanalyzed samples had a relative difference in concentration of within 20% of the original assay (Derangula et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…VMAT2 is also inhibited by the two major metabolites of tetrabenazine, α-dihyrotetrabenazine and β-dihydrotetrabenazine. Recent pharmacokinetic analyses of six healthy controls found that the time to attainment of maximum plasma concentration ( t max ) for tetrabenazine, α-dihyrotetrabenazine, and β-dihydrotetrabenazine was approximately 1 hr [8]. The terminal half-lives ( t 1/2 ) for tetrabenazine, α-dihyrotetrabenazine and β-dihydrotetrabenazine were 2.1, 7.6 and 5.9 hrs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Active isomers of 2 unrelated doses of valbenazine and deutetrabenazine within their therapeutic dosing ranges were determined at maximum plasma drug level (Cmax) following administration in separate studies. [16][17][18][19][20] Valbenazine has only 1 active isomer, and deutetrabenazine has 4, with the (-) alpha and the ( + ) beta isomers present in sufficient amounts to exert pharmacologic activity. Active isomers of deutetrabenazine and valbenazine cannot be directly compared.…”
Section: Deutetrabenazine Is a Medleymentioning
confidence: 99%